2021
DOI: 10.1093/burnst/tkab016
|View full text |Cite
|
Sign up to set email alerts
|

Combination of ablative fractional carbon dioxide laser and platelet-rich plasma treatment to improve hypertrophic scars: a retrospective clinical observational study

Abstract: Background Hypertrophic scars are one of the main complications that affect the quality of life of patients after burns. Many methods have been shown to be effective in the treatment of hypertrophic scars, such as ablative fractional CO2 laser (AFCL) and platelet-rich plasma (PRP). However, there are few studies on the effect of the combined application of these measures. The purpose of this study was to explore the therapeutic effect of AFCL combined with PRP on hypertrophic burn scars. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…However, this scale has not been used frequently, and therefore very little information is available about its reliability and validity. Nevertheless, the UNC4P has been a useful tool in the subjective evaluation of dual scar treatment interventions that involve the use of laser therapy in the treatment of scars 28–30 . However, of the patients included in the aforementioned studies, the majority were Fitzpatrick levels I–IV, while none were levels V or VI, which implicates the notable deficiency in the inclusion of dark‐skinned individuals in scar scale assessment studies.…”
Section: Resultsmentioning
confidence: 99%
“…However, this scale has not been used frequently, and therefore very little information is available about its reliability and validity. Nevertheless, the UNC4P has been a useful tool in the subjective evaluation of dual scar treatment interventions that involve the use of laser therapy in the treatment of scars 28–30 . However, of the patients included in the aforementioned studies, the majority were Fitzpatrick levels I–IV, while none were levels V or VI, which implicates the notable deficiency in the inclusion of dark‐skinned individuals in scar scale assessment studies.…”
Section: Resultsmentioning
confidence: 99%
“…However, there are some shortcomings in this study. First, in previous studies, CO 2 dot matrix laser and PRP have also been verified to have favorable efficacy on hypertrophic scars 45–47 . This study has only included patients with DS, so the efficacy of the combination on hypertrophic scars is not yet clear.…”
Section: Discussionmentioning
confidence: 97%
“…to have favorable efficacy on hypertrophic scars. [45][46][47] This study has only included patients with DS, so the efficacy of the combination on hypertrophic scars is not yet clear. Additionally, because of the small number of cases in this study, it cannot be excluded that the statistical calculation of some results may be accidental.…”
Section: Discussionmentioning
confidence: 99%
“…Hewedy et al 42 has revealed that the combination of TAC and PRP can produce better cosmetic results in the treatment of keloids and reduce the incidence of TAC‐induced side effects. Besides, Dai et al 43 has retrospectively analyzed the efficacy of ablative fractional CO 2 laser and PRP combination for the treatment of hyperplastic scars and found that combination therapy has improved efficacy over individual treatments. PRP is an emerging therapeutic in scar treatment, but its application in hypertrophic/keloid tissues is still controversial.…”
Section: Discussion and Expectationmentioning
confidence: 99%